Observer‐based non‐linear H∞ attitude control for a flexible satellite. Issue 15 (1st October 2017) - Bai, Huihui; Zhou, Yanru; Sun, Hongfei; Zeng, Jianping
Abstract : This study focuses on the observer‐based non‐linear H ∞ (OBNH) attitude control for a flexible satellite with external disturbances and local state‐region constraints. By considering the structural features of the attitude system and applying Lyapunov stability theory, the solvable conditions of the OBNH attitude control problem are provided. An advantage of this study is that the state‐feedback controller and the reduced‐order state observer can be designed independently, thus significantly reducing the complexity of the attitude control algorithm. Furthermore, based on the polynomial sum of squares (SOSs) and the generalised S ‐procedure techniques, the above problem can be transformed into a convex optimisation problem with SOS constraints. This conversion can effectively overcome the computational difficulties widely present in the control problem of non‐linear systems. Finally, a numerical example is given to illustrate the effectiveness and feasibility of the proposed approach.